Aktivitas Antioksidan dan Karakterisasi Nanopartikel Ekstrak Kulit Salak Wedi sebagai Kosmetik Antiaging - Saputri, Romadhiyana Kisno; Al-Bari, Akhmad; Nisak, Siti Khoirun; Anti, Tika Roro; Amelia, Rika (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Wedi snakefruit is one of the local species snakefruit produced in Bojonegoro Regency. Antioxidant activity in salak fruit may be influenced by its cultivar. The peel of snakefruit is reported to have antioxidant activity as in salak fruit flesh. Antioxidants can prevent free radical damage to human skin and prevent aging so can be developed in cosmetic preparations. The current trend of antiaging cosmetic preparations leads to preparations with nanoparticle size. The objectives of this study is to determine the antioxidant activity and to characterisation of nanoparticles Wedi snakefruit peel extract that will be developed as anti-aging cosmetics. Wedi snakefruit peel extract was conducted using maceration method with 96% ethanol solvent, antioxidant activity test was conducted by DPPH method and total phenol content determination method using Folin-Ciocalteu method. Nanoparticles preparation of extract by ionic gelation method with characterisation through particle measurement using PSA and zeta potential measurement. Potential antiaging activity was measured through tyrosinase inhibition testing. The results showed the IC50 value measured by DPPH method of 56.10 ppm, total phenolic content of 13.41 mg GAE/g. PSA test results showed particle size of Wedi snakefruit peel extract 884 nm and zeta sizer value of 2 mv. Tyrosine inhibitory activity of Wedi snakefruit peel extract was 63.8%. The antioxidant activity of Wedi snakefruit peel extract is in the strong category, has not met the nanoparticle requirements and has tyrosinase inhibitory activity so that it has the potential to be developed as an antiaging cosmetic.